1995
DOI: 10.1021/j100017a055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino Acid Residue Model on the Photoinduced Long-Distance Electron Transfer from the Excited Ru(bpy)32+ to Methylviologen in a Polymer Film

Abstract: Photoluminescent R~( b p y ) 3~+ complex, electron-accepting methylviologen, and an amino acid residue model compound were dispersed in a polysiloxane film, and photoinduced electron transfer from the excited Ru-( b p~) 3~+ to methylviologen and the effect of amino acid residue model on the electron-transfer distance have been studied. The electron-transfer reaction was analyzed by a static model, and the electron-transfer distance was calculated considering the distance distribution between the nearest neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…In the present study, average intermolecular distance between the acid and NBAb is estimated to be in the range of 10 -15 nm according to Poisson statistics. [20] 4.Conclusion We observed diffusion of the acids from PAG in PMMA and PEMA by using diffusioncontrolled acid-base reaction with NBAb. The method consists of measuring the decrease in absorption spectra of NBAb.…”
Section: Absorptionmentioning
confidence: 86%
“…In the present study, average intermolecular distance between the acid and NBAb is estimated to be in the range of 10 -15 nm according to Poisson statistics. [20] 4.Conclusion We observed diffusion of the acids from PAG in PMMA and PEMA by using diffusioncontrolled acid-base reaction with NBAb. The method consists of measuring the decrease in absorption spectra of NBAb.…”
Section: Absorptionmentioning
confidence: 86%
“…[8 -11] For a long-range electron transfer in a syn-thetic system, the mediation effects of 3-methylindole as a tryptophan model compound on the photoinduced electron transfer from the tris(2,29-bipyridine)ruthenium(II) complex [Ru(bpy) 3 2+ ] to methylviologen (MV 2+ ) have been investigated in a polymer membrane. [12] This result indicated that the electron-transfer distance doubled in the presence of 3-methylindole. Furthermore, it is reported that for electrochemical water oxidation in a polymer membrane, the charge-transfer distance between reactive centers increases in the presence of p-cresol from 1.28 nm to 2.25 nm, indicating that the p-cresol functions as a mediator for the charge transport.…”
Section: Introductionmentioning
confidence: 93%
“…For the C 6 Tyr systems, the charge separation is less effective at C 12 RuVQPIm despite having the best quenching efficiency; the initial rate of the viologen radical formation decreases with increasing rate of the forward reaction (quenching reaction) in the mediated process. This may be because the rate of the back reaction in the mediated process is the largest for C 12 RuVQPIm. The initial rate for the C 12 Tyr system shows the opposite length-dependence on the luminescence intensity, indicating that the initial rate directly reflects the forward reaction rate increases in the mediated process.…”
Section: Photosensitized Charge Separationmentioning
confidence: 99%
“…[14][15][16][17] It is well-known that the phosphorescence of Ru(bpy) 3 2+ is quenched by electron transfer to an acceptor such as methyl viologen (MV 2+ ). 7,8,[18][19][20][21][22][23] In the present paper we propose the polysaccharide quasisolids as a new medium for photochemical reactions. We have investigated the photoinduced electron transfer from Ru(bpy) 3 2+ to MV 2+ or propyl viologen sulfonate (PVS 0 ) ( Figure 2) in polysaccharide (agarose, κ-carrageenan) quasi-solids containing a large amount of water, by which fundamental properties of the polysaccharide quasi-solids as a medium for photochemical reactions will be discussed.…”
Section: Introductionmentioning
confidence: 99%